Numerical study of heat transfer enhancement in a solar tower power receiver, through the introduction of internal fins - Shatnawi H.; Lim C.W.; Ismail F.B.; Aldossary A. (Penerbit Akademia Baru, 2023)
In the context of solar tower power, the significance of the receiver has to do with its capacity to convert sun rays into heat. This heat is then conveyed to a heat transfer fluid. The extremely high velocity of the heat transfer fluid, motivates for the use of smart geometry to simultaneously enhance the heat transfer process and strengthen the structure of the tubes. In this study, a new molten salt receiver design was numerically investigated, following the addition of square, rectangular, circular and triangular longitudinal fins, that come at various heights (w=1,2,4 and 6 mm). Molten salt was used as the heat transfer fluid that flown through the receiver tubes with the Reynolds number ranging between 14,000 and 38,000. In comparison to a smooth tube, it was observed that while the inclusion of fins led to a dip in pressure, the overall efficiency level was improved. An increase in the number of fins, led to an improvement in the heat transfer process. The use of four square fins delivered the highest heat transfer enhancement. In the use of a singular fin, a triangular fin with a height of 1 mm delivered the best heat transfer performance. For a similar flow rate and hydraulic area, the triangular fins exhibited a better heat transfer performance than the square, circular and rectangular fins. In terms of the receiver's efficiency, the triangular fins produced the heights efficiency. 2020 PENERBIT AKADEMIA BARU - All rights reserved.